Education THE EFFECTIVENESS OF USING POETRY IN TEACHING VOCABULARY TO THE SECOND YEAR STUDENTS OF SMP NEGERI 5 LEIHITU: THE EFFECTIVENESS OF USING POETRY IN TEACHING VOCABULARY TO THE SECOND YEAR STUDENTS OF SMP NEGERI 5 LEIHITU - hanafi pelu (BDK Makassar, 2022)
The objectives of the research were to find out the effectiveness of using poetry in teaching vocabulary to the second year students of SMP Negeri 5 Leihitu and students’ interest in learning vocabulary by using poetry. The researcher applied quasi-experimental method using non-equivalent control class design. The population of this research was the second year students of SMP Negeri 5 Leihitu in academic year 2019/2020. The samples were classes VIII B and VIII C randomly selected as the experimental class and the control class. The experimental class was treated by using poetry while the control class was taught without poetry. The data were collected through vocabulary test and questionnaire. The result of the data analysis showed that there was significant difference between the students who were taught by using poetry and without poetry. The mean score of the experimental class is higher than the control class in the post test. Moreover, the result of the test indicated that the use of poetry significantly affects the students’ achievement. Then, analysis using Likert Scale shows that students are interested in learning vocabulary through poetry. It is proved by 84% students are high interest. Based on the result of analysis, the researcher concluded that the use of poetry was effective in teaching vocabulary to the second year students of SMP Negeri 5 Leihitu in academic year 2019/2020 and the students were interested in learning vocabulary by using poetry.